Empagliflozin improves cardiovascular and renal outcomes in heart failure irrespective of systolic blood pressure - Böhm, Michael; Anker, Stefan; Butler, Javed; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Mahfoud, Felix; Brückmann, Martina; Jamal, Waheed; Ofstad, Anne Pernille; Schüler, Elke; Ponikowski, Piotr; et al. (Journal of the American College of Cardiology, 2021)
Background - Empagliflozin reduces the risk of cardiovascular death or heart failure (HF) hospitalization in patients with reduced ejection fraction. Its interplay with systolic blood pressure (SBP) is not known. - Objectives - The goal of this study was to evaluate the interplay of SBP and the effects of empagliflozin in EMPEROR-Reduced (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Reduced Ejection Fraction). - Methods - Study patients (N = 3,730) were randomly assigned to groups according to SBP at baseline (<110 mm Hg, n = 928; 110-130 mm Hg, n = 1,755; >130 mm Hg, n = 1,047). This study explored the influence of SBP on the effects of empagliflozin on cardiovascular death or HF hospitalization (primary outcome), as well as on total HF hospitalizations, rate of decline in estimated glomerular filtration rate, renal outcomes, and empagliflozin’s effects and significance on SBP. - Results - Over a median of 16 months considering only patients receiving placebo, baseline SBP and the risk of cardiovascular death or hospitalization for HF (P trend = 0.0015) were inversely related. Corrected for placebo, a slight early increase was observed in SBP at <110 mm Hg, no change at 110-130 mm Hg, and a slight reduction at >130 mm Hg. These between-group differences were of borderline significance (P for interaction trend = 0.05-0.10) after 4 and 12 weeks but were not significant later. SBP at baseline did not influence the effect of empagliflozin to reduce the risk of HF events or renal endpoints. When treated with empagliflozin, patients with SBP <110 mm Hg did not have an increased rate of symptomatic hypotension. - Conclusions - Empagliflozin was effective and safe, with no meaningful interaction between SBP and the effects of empagliflozin in the EMPEROR-Reduced trial. (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Reduced Ejection Fraction [EMPEROR-Reduced]; NCT03057977)
Gesehen am 28.04.2022